A STUDY COMPARING SOCIO-DEMOGRAPHIC AND CLINICAL PROFILE OF PATIENTS OF UNIPOLAR AND BIPOLAR DEPRESSION. - Dr. Farheen fatma; Dr .Dhruv (Student's Journal of Health Research, 2023)
Background: Unipolar and bipolar depression are distinguished very distantly, in symptoms, diagnosis, prognosis, course of treatment, neurobiology, and genetics. Our study's main goal is to compare the subjective variables linked to bipolar and unipolar depression in inpatients. We also want to investigate the psychosocial and demographic factors that affect bipolar and unipolar depression. Materials and Methods: 152 patients both males and females classified, into group I (unipolar) and group II (bipolar). The clinical profile and socio-demographic profile of both were recorded. The collected data was analyzed statistically. Patients who fulfilled the inclusion criteria were included in this study. Results: The difference was significant between the two groups i.e., unipolar and bipolar depression. A value of P less than 0.05 is considered significant. 60% of the unipolar group reported severe depression without psychotic symptoms compared to 80% of the bipolar group who had severe depression with psychotic symptoms. Conclusion: With the introduction of the bipolar spectrum, it is now even more crucial to detect bipolarity in initial depression. It is important to understand the signs of the disorder to determine the precise neurobiology of bipolarity and to forecast its course, more research is required.